2013
DOI: 10.4132/koreanjpathol.2013.47.6.587
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal and Nodal Gliomatosis with Endometriosis, Accompanied with Ovarian Immature Teratoma: A Case Study and Literature Review

Abstract: Gliomatosis peritonei (GP) indicates the peritoneal implantation of mature neuroglial tissue and is usually accompanied by ovarian mature or immature teratoma. Here, we report a case of ovarian immature teratoma associated with gliomatosis involving the peritoneum, lymph nodes and Douglas' pouch, where gliomatosis coexisted with endometriosis. As far as we know, only seven cases of GP have been reported as coexisting with endometriosis. Eight cases with mature glial tissue in the lymph nodes, i.e., nodal gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…To date, eight case reports describe the association be-tween GP and endometriosis [16,18,[25][26][27][28][29][30]. Six cases were associated with immature teratoma, while the remaining cases involved a mature teratoma as in the present case.…”
Section: Discussionmentioning
confidence: 69%
“…To date, eight case reports describe the association be-tween GP and endometriosis [16,18,[25][26][27][28][29][30]. Six cases were associated with immature teratoma, while the remaining cases involved a mature teratoma as in the present case.…”
Section: Discussionmentioning
confidence: 69%
“…3 The spread of GP to lymph nodes has been documented as well as the coexistence with endometriosis. 4 In the CT are observed as multiple peritoneal nodules of variable size or omental cake. During surgery, the macroscopic appearance is similarly to carcinomatosis, peritoneal tuberculosis, endometriosis, ectopic decidua, peritoneal leiomyomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…In some reports, GP was only found in the second surgery (as in case 4 in the present study). Kim et al reviewed about 100 cases in the literature and found 9 cases of nodal gliomatosis in the pelvic or para-aortic lymph nodes with or without the presence of GP [ 6 ]. However, in their literature review, there were three cases of nodal gliomatosis presented as grades 1 to 3.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of glial tissue in lymph nodes is rare. Thus far, 14 cases have been reported in nine articles [ 6 , 8 , 13 – 18 ] (Table 2 ). Based on previous reports, adjuvant chemotherapy is unnecessary for patients with retroperitoneal lymph node metastasis of mature glial tissue.…”
Section: Discussionmentioning
confidence: 99%